Innovation dans un projet de télécollaboration orale en intercompréhension : bilan et perspectives du projet IOTT - Sandra Garbarino; Paola Leone (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication, 2020)
The paper aims at assessing a telecollaboration learning project named Intercompréhension Orale et Teletandem (IOTT), developed by University of Lyon 2 and University of Salento. It also points to the learning potential of plurilingual computer mediated synchronous communication across two different disciplines: an intercomprehension program and a foreign language teaching methodology course. After describing the pedagogical design (eg the activities carried out at international and local levels), the article offers a methodology (Cros, 2004) which allows authors to self-evaluate the project with regard to its effectiveness in the attainment of the desired results. Strengths and weaknesses are discussed, highlighting domains for gaining a deeper understanding of the scenario and for enhancing a theoretically enriched bottom-up analysis. The focal points of the proposed assessment are IOTT innovative features in relation to preceding Teletandem-based learning scenarios and to other intercomprehension online teaching/learning experiences. The evaluation process focuses as well on transformation and changes in educational values and practices. Data collected by means of questionnaires, learning diaries, videorecordings of oral teletandem sessions and interviews with students show learners perceptions of the experience. The assessment of IOTT is carried out bearing in mind the improvement of its pedagogical design in order to optimize learning in future teletandem projects for plurilingual education.